Knowledge and Practice of Sexual Education Teacher of Special Needs Students - Siti Khadijah Johan; Mohd Hanafi Mohd Yassin (Department of Special Education, 2019)
The problem of sexual behavior among Special Needs Students can be overcome by the effectiveness of teaching or presentation in Sexual Education lesson. In this regard, the study aims to identify the relationship between knowledge level and Sexual Education practice of Special Needs Students Special Education teacher. This study was based on cognitive theory that emphasizes internal mental processes. The model used in this study was the Model of Cognitive Response. This quantitative study conducted cross-sectional surveys on 86 special education teachers in Kulai, Johor, Malaysia. The sample was selected through stratified random sampling technique to balance the number of samples comprising male teachers and female teachers. The research instrument was adapted from Ang Chai Tin’S study in year of 2014. All the questionnaires showed the reliability level of 0.801 Cronbach’s Alpha coefficient. The data obtained from questionnaires were distributed to teachers. Data were analyzed via SPSS and described with descriptively as well as inferentially. The findings of the Spearman Correlation Coefficient indicated that there was a relationship between the level of knowledge and the teaching practice of Special Needs Students Sexual Education among teachers. [rs = 0.664, n=86, p < 0.05]. Correlation strength value was strong. The conclusions of this study showed that Null Hypothesis (Ho) rejected, knowing that there was a strong and significant positive relationship between the level of knowledge and the level of teacher practice in MBK Sexual Education.